SWELLING BEHAVIOR OF POLY (AAM_MA) HYDROGEL MATRIX AND STUDY EFFECTS PH AND IONIC STRENGTH, ENFORCEMENT IN CONTROLLED RELEASE SYSTEM - Karam, Faiq F.; Alzayd, Asawer A. Mhammed (International Journal of Applied Pharmaceutics, 2018)
Objective: The objective of this study was to estimate the performance of Acrylamide-malice acid (AAM_MA) hydrogel preparatory by free radical polymerization to loading/release Atenolol and Ciprofloxacin drugs from aqueous solution to be used in a controlled release system. Methods: Free radical polymerization method has been used to prepare (AAM-MA) hydrogel. The prepared hydrogel was characterized by Fourier transform infrared (FTIR), Thermal Gravimetric Analysis/Derivative Thermal Gravimetric (TGA/DTG) and Field Emission Scanning Electron Microscopy (FE-SEM) techniques. The pH-dependent swelling behavior was investigated in addition to the effective ionic strength on adsorption and release system of the drug in vitro. Results: Results showed that the highest swelling ration in pH=7.4 and the same value of pH for the release of the drug. Thermal analysis test for prepared hydrogel showed good thermal stability. The hydrogel showed a negative effect with an increase saline contact Calcium carbonate appeared to have highly effect on releasing drugs from the polymeric network. Conclusion: Higher ability of poly (AAM-MA) hydrogel to act as a carrier for the Ciprofloxacin and Atenolol with highest swelling and releasing under following conditions: at pH 7.4, at temperature 37 Â°C and the effect of ionic strength (charge/ratio) which indicate that the smaller radius have less effect on release and the largest charge have negative effect on release ratio that attributed to cation formation inter and intra complex surface hydrogel. Â